Allometric equations for estimating above and belowground biomass of Colophospermum mopane in Mozambique - Sá Nogueira Lisboa; Severino Macôo; Almeida Alberto Sitoe (Scientific Reports)
Abstract Seasonally dry tropical woodlands are vital for climate change mitigation, yet their full potential in carbon storage remains poorly understood. This is largely due to the lack of species-specific allometric models tailored to these ecosystems. To address this knowledge gap, this study aimed to develop species-specific biomass allometric equations (BAEs) for accurately estimating both above- and below-ground biomass of Colophospermum mopane (J.Kirk ex Benth.) J.Kirk ex J. Léonard, and to assess the feasibility of incorporating total height, estimated using height-diameter (H-D) equations, to improve the accuracy of biomass estimation in Mozambique. We applied a destructive method and felled 120 C. mopane trees in Mabalane and Tambara Districts. We measured breast height diameter (D), total height (H) and biomass of each component (roots, stem, branches and leaves). We fitted three BAE models using Ordinary Least Squares (OLS) regression and fifteen H-D models using nonlinear regression. A validation procedure checked the applicability of all models. We conducted a forest inventory with 78 temporary clusters, each consisting of four 100 m x 20 m plots, to estimate the average AGB and BGB of C. mopane using the best-fitting BAE and H-D model. We also compared the best BAE of C. mopane with existing locally developed species-specific BAEs. The study found that the model including the interaction of D 2 and H, performed better than the model with separate D and H. However, models with D and H performed similarly to models with D alone. The Power model with two parameters and the HossfeldIV model with three parameters exhibited the best performance among the H-D models. Integrating the H from the H-D model into the BAE for AGB estimation can improve the efficiency and reliability of biomass estimation from forest inventory data. This research is timely as there is an urgent need to improve the accuracy of carbon counting to support climate change goals and sustainable management of Mopane woodland given their spatial extent in southern Africa.